2011
DOI: 10.1021/jp200212g
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Micelles of a Nonionic Block Copolymer Determined by SANS and SAXS

Abstract: The micellar state of Pluronic P123, which is a poly(ethylene oxide)-b-poly(propylene oxide)-b- poly(ethylene oxide) block polymer (EO(20)PO(70)EO(20)), has been investigated using SANS, SAXS, and differential scanning calorimetry under the conditions utilized in the synthesis of ordered mesoporous materials, such as SBA-15. The absolute intensity measurements, both with SANS and SAXS, have provided a detailed quantitative description of the P123 micelles in the framework of a simple core-shell spherical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
155
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 31 publications
13
155
1
1
Order By: Relevance
“…These estimates of the aggregation numbers are entirely consistent with the measured P123 diffusion rates. [34] and Soni et al [40] b: Micelles number density value is in good agreement with the values reported by Manet et al [41] Significant changes in micelle morphology are observed when small molecule surfactants are added to the P123/alcohol systems. Take for example the SDS case, on addition of 50 mM SDS to the 5 wt% P123 aqueous and alcohol/aqueous solutions, Figure 3, SANS data show significant loss in the scattering intensity and the emergence of correlation peaks at higher Q values which together indicates the formation of smaller, mixed, charged micelles.…”
Section: Effect Of Alcohols On the Pluronic Micelle Structure Scattesupporting
confidence: 87%
“…These estimates of the aggregation numbers are entirely consistent with the measured P123 diffusion rates. [34] and Soni et al [40] b: Micelles number density value is in good agreement with the values reported by Manet et al [41] Significant changes in micelle morphology are observed when small molecule surfactants are added to the P123/alcohol systems. Take for example the SDS case, on addition of 50 mM SDS to the 5 wt% P123 aqueous and alcohol/aqueous solutions, Figure 3, SANS data show significant loss in the scattering intensity and the emergence of correlation peaks at higher Q values which together indicates the formation of smaller, mixed, charged micelles.…”
Section: Effect Of Alcohols On the Pluronic Micelle Structure Scattesupporting
confidence: 87%
“…They showed that the overall size of P123 micelles increase following the Hofmeister anions series due to their salting-in/out properties: NO 3´< Br´< Cl´< SO 4 2´< H 2 PO 4´ [ 37]. The salting-out ions Cl´, SO 4 2´a nd H 2 PO 4´d o not show a specific tendency to confine within the micelles.…”
Section: Acid Source and Acid/al Ratiomentioning
confidence: 99%
“…Therefore micelle sizes in their presence are similar. As¨NO 3´i s a salting-in ion, its concentration in the outer shell of P123 micelles-composed of hydrophilic EO blocks-should be higher than in the bulk solution [37,38], whereas the concentration of salting-out ions is homogeneous. Ordered mesoporous alumina are thought to form through interactions between charged alumina colloids and the EO blocks of the surfactant [39].…”
Section: Acid Source and Acid/al Ratiomentioning
confidence: 99%
“…[8,9] In particular, Pluronics have found a niche in this area. [9,10] Pluronics are commericaly available block copolymers of poly 15 (ethylene oxide) and poly(propylene oxide). Pluronic P123, for instance, is used to sythesise SBA-15 mesoporous silica.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The initial structure of polymer micelles and their modification (by temperature, pH and solubilisation of hydrophobic oils) strongly impact the final mesoporous structure of hybrid materials. [9,10] Other common applications of Pluronics in-20 clude detergency, emulsification and fermentation. [11,12] For this reason, there is an abundance of literature dealing with solubilisation by Pluronics.…”
Section: Introductionmentioning
confidence: 99%